The Effect of Size Reduction and Preparation Duration on The Antioxidant Activity of White Saffron (Curcuma mangga Val.) - Pujimulyani, Dwiyati; Raharjo, Sri; Marsono, Y; Santoso, Umar (Journal of Food and Pharmaceutical Sciences, 2013)
Food processing is usually conducted through preparation stages such as peeling, slicing, or cutting. The purpose of this research was to determine the correlation between the antioxidant activity and the total phenolic compounds of white saffron as affected by different level of size reduction and the duration of rhizome preparation at room temperature. White saffron rhizomes were peeled, washed, and cut into 1x1x1 cm3. The whole white saffron was sliced diagonally at thickness of 4 x 2 mm, and grated. The antioxidant activity of the white saffron was determined by radical scavenging activity using 2-2-diphenyl-1-picrylhydrazyl (DPPH) radical and by ferric reducing antioxidant power FRAP) method. The total phenol and total flavonoid contents were also determined at 2, 4, and 6 hours, respectively. The result showed that the antioxidant activities, total phenolic and flavonoid contents due to the preparation of whole white saffron for 6 hour are not statistically different compared to those of fresh white saffron. The preparation of white saffron sliced at 2 mm and grated for 2 hour showed a significant decrease in the antioxidant activities, compared to those of fresh white saffron.Keywords: white saffron, preparation duration, antioxidant activity, total phenol